(untitled) (Damascus University Journal of Historical Studies, 2022)
Hassan Al-Taweel, the most important prince of the "white sheep" tribes, fought many wars and internal battles until he was able to settle on the throne of his kingdom in Diyarbakir. After the matter was settled internally, he was able to raise his tribe, the Ak Qoyunlu, to a force for which a thousand accounts could be reckoned. Moreover, after he consolidated the pillars of his rule internally, he began to expand in the west and east and oppose the Mamluks and the Ottomans, and he caused them trouble by seizing their lands. He believed that he could become the most important Islamic force in the East if European countries helped him, so he communicated with them and received all the welcome and support from them. He did not take into account that the Ottomans and the Mamluks could unite against him and block the way for his ambitions. Perhaps, it was the misfortune of Hassan Al-Taweel that the Sultan of the Ottomans at the time was Muhammad the Conqueror, who overthrew Constantinople by his own hand, this impregnable fortress that his predecessors were unable to seize. Consequently, he did not hesitate to eliminate the danger of Hassan al-Taweel and put an end to his ambitions, which would be an obstacle to the expansionist Ottoman ambition.